Genome-wide characterization of phospholipase D family genes in allotetraploid peanut and its diploid progenitors revealed their crucial roles in growth and abiotic stress responses - Zhang, He; Yu, Yang; Wang, Shiyu; Yang, Jiaxin; Ai, Xin; Zhang, Nan; Zhao, Xinhua; Liu, Xibo; Zhong, Chao; Yu, Haiqiu (Frontiers in Plant Science, 2023)
Abiotic stresses such as cold, drought and salinity are the key environmental factors that limit the yield and quality of oil crop peanut. Phospholipase Ds (PLDs) are crucial hydrolyzing enzymes involved in lipid mediated signaling and have valuable functions in plant growth, development and stress tolerance. Here, 22, 22 and 46 PLD genes were identified in A. duranensis, A. ipaensis and A. hypogaea, respectively, and divided into α, β, γ, δ, ε, ζ and φ isoforms. Phylogenetic relationships, structural domains and molecular evolution proved the conservation of PLDs between allotetraploid peanut and its diploid progenitors. Almost each A. hypogaea PLD except for AhPLDα6B had a corresponding homolog in A. duranensis and A. ipaensis genomes. The expansion of Arachis PLD gene families were mainly attributed to segmental and tandem duplications under strong purifying selection. Functionally, the most proteins interacting with AhPLDs were crucial components of lipid metabolic pathways, in which ahy-miR3510, ahy-miR3513-3p and ahy-miR3516 might be hub regulators. Furthermore, plenty of cis-regulatory elements involved in plant growth and development, hormones and stress responses were identified. The tissue-specific transcription profiling revealed the broad and unique expression patterns of AhPLDs in various developmental stages. The qRT-PCR analysis indicated that most AhPLDs could be induced by specific or multiple abiotic stresses. Especially, AhPLDα3A, AhPLDα5A, AhPLDβ1A, AhPLDβ2A and AhPLDδ4A were highly up-regulated under all three abiotic stresses commonly, whereas AhPLDα9A was neither expressed in 22 peanut tissues nor induced by any abiotic stresses. This genome-wide study provides a systematic analysis of the Arachis PLD gene families and valuable information for further functional study of candidate AhPLDs in peanut growth and abiotic stress responses.